Sustainable Development Disclosure in ESG Reports and Gender Diversity on the Audit Committee - Alina, Aisyah; Durriya, Azalia (Advances in Accounting Innovation, 2024)
Objective: The aim of this research is to examine the impact of gender diversity in audit committees on the quality of Environmental, Social, and Governance (ESG) disclosures made by companies listed on the Indonesian Stock Exchange between 2018 and 2023.Methods: Financial databases and annual reports of 673 companies served as data sources. ESG disclosures were assessed based on Information ratings for Completeness, Relevance, and Accessibility, which measure the quality of disclosures. The Blau index and proportion of female members in the audit committee are used to measure gender diversity. To address endogeneity issues, a three-stage least squares methodology was used.Findings: The study reveals that having a greater representation of different genders in audit committees greatly improves the thoroughness and pertinence of ESG disclosures. However, it does not have a significant effect on their ease of access. Furthermore, the level of activity of the audit committee has a favorable effect on the association between gender diversity with the level of ESG disclosures. This suggests that audit committees with a diverse composition and lower levels of busyness are more successful in improving ESG reporting.Novelty: This study offers fresh perspectives on how gender diversity might enhance the accuracy and completeness of ESG disclosures. It also emphasizes the role of audit committee workload in shaping this relationship, providing a deeper comprehension of the elements that impact ESG reporting.Theory and Policy Implications: The conclusions are based on the principles of Representation Theory, which propose that including a variety of views enhances the quality of decision-making and supervision. The findings suggest that enhancing gender diversity in audit committees can enhance the quality of ESG reporting. It is recommended that policymakers and organizations improve the representation of different genders in audit committees and effectively handle the workload of these committees in order to maximize the quality of environmental, social, and governance (ESG) disclosures.